Determination of Fiscal Dependence and Disaster Risk on Local Government Unexpected Expenditure Allocation in Indonesia - Arif Wicaksana , Francis Lucky; Azhar, Azhar (PERSPEKTIF, 2025)
Indonesia's vulnerability to natural disasters significantly challenges local government fiscal management and disaster preparedness. This study examines the relationship between budgetary dependence and disaster risk index on the allocation of contingency expenditures  (BTT) in local governments in Indonesia. This study analyzes how fiscal dependence and regional disaster risk index affect local government decisions in preparing resources to anticipate emergencies. This research is academically relevant because of the limited studies linking fiscal governance and disaster risk in developing countries, particularly Indonesia. The study uses a quantitative approach with correlation analysis of regency/city government budget data throughout Indonesia in 2023. The study's results show that the level of fiscal dependence or the disaster risk index does not entirely determine the allocation of BTT by local governments. Although there is a significant negative correlation between disaster risk scores and unexpected spending allocations, the relationship is weak. This indicates that other factors play a greater role in BTT budgeting decisions. In the context of policy, the results of the study recommend the development of regulations that encourage local governments to allocate unexpected spending budgets proportionally according to the level of risk faced, so that regional fiscal readiness in dealing with emergencies can be more optimal. Academically, this study enriches the literature on fiscal governance in developing countries by including disaster risk variables as an essential factor in regional budgeting.